Prolene suture-assisted cystoscopic removal of double J ureteral stents in infants - Zeng, Xinhao; Lian, Na; Liu, Tong; Wang, Xiaoyong (Frontiers in Pediatrics, 2025)
ObjectivesThe purpose of this study was to describe the prolene suture-assisted cystoscopic removal of double J ureteral stents in infants and summarize the safety, operability, and effectiveness of this approach.MethodsThe clinic data of patients who underwent double J ureteral stent removal by prolene suture-assisted cystoscopy were reviewed. The operation procedure was as follows: First, a folded 4-0 prolene suture was preset into the cystoscope sheath, and the telescope was placed. Second, the cystoscopy was performed by inserting the cystoscope into the urinary bladder and finding the end of the double J ureteral stent under cystoscopy. Subsequently, the folded suture was pushed out of the sheath to form a coil that was used to hook 1–2 cm of the end of the stent. Finally, the stent was caught by tightening the prolene coil while the cystoscope was retracted into the cystoscope sheath; the removal was accompanied by exiting the cystoscope. Cystoscopy was repeated to confirm no additional damage.ResultsOverall, 15 double J ureteral stents were retrieved in 15 infants, whose average age was 3.78 ± 1.2 months, average weight was 5,951 ± 797 g, average residence time of the stents in the ureter was 31.20 ± 2.14 days, and the average operation time was 3.5 ± 1.2 min. No complications, such as urethral injury, occurred during the operation.ConclusionsProlene suture-assisted cystoscopy is one of the simple, safe, and effective technique for the removal of double J ureteral stents, especially suitable for infants or patient in whom the grasping forceps cannot pass through the matching cystoscope sheath.